The Impact of Green Economy Public Policy on Green Industry Sector Investment - Idrus, Sitti Hairani; Jaya, Laode Muhammad Golok; Yusuf, Muhammad; Unga, Wa Ode Harliyanti; Bakti, Bakti (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study explores the impact of green economy public policies on investment in the green industry sector. The transition to a green economy, driven by environmental sustainability goals, has led to significant policy changes aimed at promoting eco-friendly practices across various sectors. This research uses a qualitative literature review method to examine existing studies, reports, and academic papers on how public policies related to green economy initiatives influence investments in green industries. Key areas of focus include the role of government incentives, regulatory frameworks, market demand for sustainable products, and the financial risks and opportunities associated with green investments. The findings suggest that effective green economy policies can attract investments by providing financial incentives, reducing risks, and fostering innovation in clean technologies. However, challenges such as inadequate policy implementation, lack of awareness, and financial barriers still hinder the growth of green industry investments. This study contributes to the understanding of how green economy policies can shape investment flows in the green industry sector and provides recommendations for improving policy effectiveness to drive sustainable economic growth.